Simetria central na teoria das matrizes: uma investigaçao sobre matrizes centrossimétricas - Amorim, Lucas Costa (Universidade Federal de São Carlos, 2025)
This study aims to investigate the development of centrosymmetric matrices over the years. To do so, we will analyze authors who conducted research on the determinant, the inverse, the eigenvalues, and the eigenvectors of centrosymmetric matrices. The investigation will encompass an analysis of primary and secondary sources, with the goal of outlining the historical context in which centrosymmetric matrices emerged as a distinct topic of mathematical research. By analyzing these historical roots, we will be able to establish the foundations of the early development of centrosymmetric matrices. Subsequently, this study will focus on four main milestones: the calculation of the determinant, the inverse, the eigenvalues, and the eigenvectors of centrosymmetric matrices. Exploring the relationship between these studies and how they complemented each other will be essential to understanding the progression of knowledge in this field. As we advance in this historical investigation, we will gain a deeper understanding of the origins and evolution of centrosymmetric matrices. This understanding will allow us to better contextualize the significant contributions of Zehfuss, Muir, Hanus, Ray, and Good, as well as recognize the importance of these advancements in shaping modern understanding of matrices and their applications.
Central symmetry in matrix theory: an investigation on centrosymmetric matrices
Simetría central en la teoría de matrices: una investigación sobre matrices centrossimétricas
Keywords: Matrizes centrossimétricas; Determinante; Autovalor; Autovetor; Inversa; CIENCIAS EXATAS E DA TERRA::MATEMATICA; 4. Educação de Qualidade